2021
DOI: 10.1136/heartjnl-2021-319290
|View full text |Cite
|
Sign up to set email alerts
|

Education on cardiac risk and CPR in cardiology clinic waiting rooms: a randomised clinical trial

Abstract: ObjectiveWaiting time is inevitable during cardiovascular (CV) care. This study examines whether waiting room-based CV education could complement CV care.MethodsA 2:1 randomised clinical trial of patients in waiting rooms of hospital cardiology clinics. Intervention participants received a series of tablet-delivered CV educational videos and were randomised 1:1 to receive another video on cardiopulmonary resuscitation (CPR) or no extra video. Control received usual care. The primary outcome was the proportion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 24 publications
(21 reference statements)
0
21
0
Order By: Relevance
“…Potential implications of these findings include consideration of a more productive use of this time in ambulatory clinics, such as implementing interventions during this time that can improve health literacy and may improve health outcomes and satisfaction with health services. 25,26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential implications of these findings include consideration of a more productive use of this time in ambulatory clinics, such as implementing interventions during this time that can improve health literacy and may improve health outcomes and satisfaction with health services. 25,26…”
Section: Discussionmentioning
confidence: 99%
“…Potential implications of these findings include consideration of a more productive use of this time in ambulatory clinics, such as implementing interventions during this time that can improve health literacy and may improve health outcomes and satisfaction with health services. 25,26 The interaction between SES and time to accessing health services has been debated for over 20 years. Most data are derived from elective surgery waiting lists, 13,27 and there is some evidence discrimination is reversing as new policies are introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Visual communication aides such as images, videos and heart models may be an effective delivery technique [38,66,[75][76][77]. Patients prefer positive images that are colourful and engaged with text, and images of real people rather than cartoons [76].…”
Section: Visual Materialsmentioning
confidence: 99%
“…Visual communication is also successfully used across digital platforms. For example, greater patient satisfaction was reported when receiving SMS text messages that included a visual aide [76], and tablet-delivered waiting room education increased motivation to improve cardiovascular health-related behaviours [77].…”
Section: Visual Materialsmentioning
confidence: 99%
“…The potential impact of patient education on improving outcomes in patients with cardiovascular disease (CVD) has received little attention. In a randomised clinical trial, McIntyre and colleagues 1 found that waiting room video-based education about CVD risk reduction resulted in more patients being motivated to implement heart healthy behaviours (29.6% vs 18.7%, relative risk 1.63, 95% CI 1.04 to 2.55) and higher levels of satisfaction with the clinic visit. Participants who were also randomised to receive education about cardio-pulmonary resuscitation (CPR) reported greater confidence in performing CPR.…”
mentioning
confidence: 99%